1985
DOI: 10.1016/s0022-5347(17)48877-x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Transvascular Embolization in the Treatment of Renal Carcinoma

Abstract: In a consecutive series of 62 patients with renal carcinoma transvascular embolization has been evaluated in regard to its limitations, complications, influence on the surgical procedure and success of treatment. Of 47 planned embolizations 36 could be accomplished. Total embolization was achieved in 29 of the 36 cases (81 per cent). One case was complicated due to displacement of the embolization material to the femoral artery. The subjective impression of the surgeon was that embolization facilitated nephrec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The same results were shown in more extensive tumors of stages T3/T4 as well as in tumors with a renal vein infiltration and regional lymph node metastases. In all the stages mentioned, we have been unable to demonstrate any statistically significant difference with regard to intraoperative blood loss and the duration of operation between the two groups, which is in concordance with other investigations (3,10,11). Only GIULIANI et coll.…”
Section: Discussionsupporting
confidence: 91%
“…The same results were shown in more extensive tumors of stages T3/T4 as well as in tumors with a renal vein infiltration and regional lymph node metastases. In all the stages mentioned, we have been unable to demonstrate any statistically significant difference with regard to intraoperative blood loss and the duration of operation between the two groups, which is in concordance with other investigations (3,10,11). Only GIULIANI et coll.…”
Section: Discussionsupporting
confidence: 91%
“…However, opinions on the role of preoperative RAE in the management of patients with RCC are controversial. Although a significant number of studies on RAE are reported in these patients, there is no consensus on the benefits and morbidity associated with the procedure [4–6]. Moreover, many large studies on the use of RAE were conducted in the 1980s, before the development of improved techniques and imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The technique of transcatheter embolization has been applied pre-operatively to both the primary tumor before nephrectomy [8,9] and metastatic bony lesions [10 Á13] to limit intra-operative blood loss. Selective transcatheter embolization of RCCa osseous metastases offers a reasonable and rational therapeutic approach for pain relief in this patient population.…”
mentioning
confidence: 99%